Mechanical characterisation of water-jet shot peened H13 tool steel surface - Anati, N.; Aqida, S. N.; Ismail, Nurazima; Kasim, M. S. (Faculty Mechanical Engineering, UMP, 2022)
A wear-resistant surface is achievable via the surface treatment of various sources such as laser, water-jet, ion beam, and plasma. This paper investigates the parameters of water-jet shot-peened H13 tool steel for minimum surface roughness and maximum hardness properties. Water jet processing parameters are significant in determining the surface roughness as well as hardness properties. Water-jet shot-peened (WJSP) was used in this experiment to improve the surface properties of H13 tool steel. The parameters are pressure and feed rate of 172 MPa to 310 MPa and 2600 mm/min to 10000 mm/min. The shot-peened samples were characterised for surface topography, surface roughness, and hardness properties. A laser confocal microscope was used to determine the dimension of the modified surface from shot peening and average surface roughness. Hardness properties were measured using the Vickers scale. From topography analysis, the surface roughness reading on the shot-peened surface was measured as much as 6.88 µm to 14.06 µm. Minimum surface roughness measured was 6.88 µm on sample processed at pressure and feed rate 172 MPa and 2600 mm/min. The hardness properties of the shot-peened subsurface were between 196 HV and 227 HV. The resulted hardness properties were due to plastic deformation from abrasive particle bombardment during shot peening. The findings are important to designing enhanced surface properties for mould and die applications.